The relationship between body mass index and the variation in plasma levels of triglycerides after short-term red wine consumption - Cesena, Fernando Henpin Yue; Coimbra, Silmara Regina; Andrade, Ana Cristina Magalhães; da Luz, Protásio Lemos (Journal of clinical lipidology, 2011)
Alcoholic beverages may have protective cardiovascular effects but are known to increase the plasma levels of triglycerides (TG). Both TG and the ratio of TG to high-density lipoprotein cholesterol (TG/HDL-cholesterol) are associated with increased cardiovascular risk. To determine the predictive factors for variations in plasma levels of TG and the TG/HDL-cholesterol ratio in patients after they had consumed red wine for 14 days. Forty-two subjects (64% men, 46 ± 9 years, baseline body mass index [BMI] 25.13 ± 2.76 kg/m 2) were given red wine (12% or 12.2% alc/vol, 250 mL/day with meals). Plasma concentration of lipids and glucose were measured before and after red wine consumption. Blood was collected after 12 hours of fast and alcohol abstention. Red wine increased plasma levels of TG from 105 ± 42 mg/dL to 120 ± 56 mg/dL ( P = .001) and the TG/HDL-cholesterol ratio from 2.16 ± 1.10 to 2.50 ± 1.66 ( P = .014). In a multivariate linear regression model that included age, baseline BMI, blood pressure, lipids, and glucose, only BMI was independently predictive of the variation in plasma TG after red wine (beta coefficient 0.592, P < .001). BMI also predicted the variation in TG/HDL-cholesterol ratio (beta coefficient 0.505, P = .001, adjusted model). When individuals were divided into three categories, according to their BMI, the average percentage variation in TG after red wine was –4%, 17%, and 33% in the lower (19.60−24.45 kg/m 2), intermediate, and greater (26.30−30.44 kg/m 2) tertiles, respectively ( P = .001). Individuals with higher BMI, although nonobese, might be at greater risk for elevation in plasma TG levels and the TG/HDL-cholesterol ratio after short-term red wine consumption.